The Relationship of Some Psychological Skills to the Leading Personality of Police College Students - Marwa Tariq Kazem1 , Shaima Ali Khamis2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The performance of the policeman is usually achieved when it is fine-tuned and trained in order to reachthe graduation of policemen who are able to defend the country and the security and comfort of citizens,and that leadership is a valuable characteristic of the character that must be met by the men of the InternalSecurity Forces who are assigned leadership tasks in The future after their graduation, and because the policecollege students are the protectors of the homeland in the future, and through the researchers ’meeting with anumber of police college students’ trainers, there has appeared weakness or lack of interest in the leadershipaspects during training that affect students ’performance and the extent of their impact on their personalityafter graduation, so the researchers saw knowledge Do some psychological skills have a relationship inthe formation of the leadership personality of the police college students, and the research objectives wereto identify some psychological skills (the ability to focus attention, the ability to relax, the ability to faceanxiety among the police college students and to reveal the relationship between psychological skills andthe leadership character of Students of the Police College, and knowing the level of leadership personalityamong students of the Police College. As for the research assumption, there is a moral correlation betweensome psychological skills and the formation of the leading personality of students Police College Theresearchers used the descriptive approach in the style of survey studies to suit the nature of a problem. As forthe research sample, the students of the Police College, through the results of the research, the researchersconcluded that the leadership personality was greatly affected by relaxation, and this was evident duringthe results of the research, and the leadership personality was affected Great concern and this was evidentthrough the search results.